Rational drug therapy of chronic heart failure: the role of mineralocorticoid receptor antagonists: review - Natalia V. Safronova; Igor V. Zhirov; Sergey N. Tereshchenko (ZAO "Consilium Medicum", 2022)
Mineralocorticoid receptor antagonists (MRAs) are part of basic medical therapy for heart failure. The clinical efficacy of MRAs has been proven by randomized clinical trials. To review comparative efficacy and tolerability data between the two main MRAs, spironolactone and eplerenone, in patients with systolic heart failure.